Contextual numeracy learning through a culturally responsive–ethnomathematics (CReM) model using Joglo Jompongan architecture - Westhy Devananda Putri; Ida Dwijayanti; Nizaruddin Nizaruddin (Universitas Hamzanwadi, 2026)
Although research on culturally responsive pedagogy and ethnomathematics continues to grow, empirically grounded models for systematically integrating cultural contexts into numeracy-oriented geometry instruction remain limited. This study aimed to develop and evaluate a contextual numeracy learning model based on Culturally Responsive–Ethnomathematics (CReM) using the architectural features of the Joglo Jompongan. Research and Development (R&D) with design thinking was employed with 22 junior high school equivalent learners at a Community Learning Activity Center (Package B). Data were collected through interviews, classroom observations, and student activity sheets and were analyzed descriptively. The findings indicate notable improvements in students’ understanding of plane and solid geometry, as well as in their ability to connect mathematical concepts with culturally situated contexts. High levels of learning engagement and cultural awareness were also observed. Embedding geometric ideas within familiar architectural elements supported students’ construction of mathematical meaning from lived experiences, offering an adaptable framework for culturally responsive and conceptually grounded numeracy instruction.